Respon Guru Matematika terhadap Keberlangsungan Belajar Siswa Selama Pandemi - Apriani, Maria Suci; Rianasari, Veronika Fitri; Julie, Hongki (Edumatica : Jurnal Pendidikan Matematika, 2021)
The continuity of student learning in the midst of a pandemic is important. This encourages teachers to choose priorities in implementing distance learning. Teachers' efforts to accommodate inclusive learning in the midst of social and economic challenges and gaps in distance learning are a step in realizing student learning sustainability in the midst of a pandemic. The research conducted on 374 Mathematics teachers in Indonesia aims to determine the responses of Mathematics teachers to the continuity of student learning during the pandemic. These responses are seen from the teacher's priorities in distance learning and the efforts made in implementing inclusive learning during the pandemic. This research is descriptive research. Sampling was done using snowball sampling technique. Data collection was done by distributing online questionnaires. Several semi-open questions were asked which were then analyzed qualitatively using the Miles and Huberman framework and using descriptive statistics. The results showed that 81,18% teachers still prioritize the right of students to continue to acquire knowledge, by not pursuing the achievement of curriculum targets. To accommodate these student rights, teachers were encouraged to carry out inclusive learning. As many 100% teachers tended to apply the principles of flexible learning and 0,94% teachers collaborated with the student's parents by apllying the type of communication initiated by Epstein, namely by designing effective communication with parents through home visit activities.